2015
DOI: 10.1007/978-1-4939-2432-5_3
|View full text |Cite
|
Sign up to set email alerts
|

U1 interference (U1i) for Antiviral Approaches

Abstract: U1 snRNP (U1 small nuclear ribonucleoprotein) is an essential component of the splicing machinery. U1 snRNP also plays an additional role in 3'-end mRNA processing when it binds close to polyadenylation sites (PAS). Cotranscriptionally, U1 snRNP binding close to putative PAS prevents premature cleavage and polyadenylation and consequently safeguards pre-mRNA transcripts and defines promoter directionality. At the 3'-end of mRNAs, U1 snRNP binding to putative PAS may regulate mRNA length or inhibit polyadenylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 56 publications
0
7
0
1
Order By: Relevance
“…With the exception of the case of F30 insulators, experiments obtained thus far suggest that stronger inhibitions by U1 snRNP could result in better inducibility after TC-mediated structural shifts. We have previously shown that multiplexing U1 BSs leads to synergistic inhibitions (reviewed in refs and ). Thus, we combined U1in and U1out riboswitches in the reporter cassette with the aim of increasing the dynamic range of the system (Figure a).…”
Section: Resultsmentioning
confidence: 99%
“…With the exception of the case of F30 insulators, experiments obtained thus far suggest that stronger inhibitions by U1 snRNP could result in better inducibility after TC-mediated structural shifts. We have previously shown that multiplexing U1 BSs leads to synergistic inhibitions (reviewed in refs and ). Thus, we combined U1in and U1out riboswitches in the reporter cassette with the aim of increasing the dynamic range of the system (Figure a).…”
Section: Resultsmentioning
confidence: 99%
“…Although the C25G base change did not result in an improvement in the splicing of the Dup51p reporter, the improvement in binding of U1-70K was significant. Modified U1 snRNAs carrying base changes to their 5′-regions are widely used for correction of adverse effects of mutant 5′-ss, and it may be worthwhile to test if the C25G base change in the engineered U1 snRNAs enhances splicing of other targets ( Blázquez and Fortes 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the experience concerning therapeutic targeting of splicing is far more advanced, the general proof-of-concept of targeting specific polyadenylation sites for redirection of processing based on analogous approaches has been made. This includes the use of ASOs [ 179 ] and siRNAs [ 178 ] as well as modified U1 snRNP, which interacts with a target gene upstream of its PAS to regulate gene expression [ 14 ].…”
Section: Targeting Mrna 3′ End Formation As a Novel Therapymentioning
confidence: 99%